ShadeMotion: Applications of an open-source canopy shade-modelling software in post-secondary curricula, short-term training workshops, and demonstration farms across Latin America for climate-resilient agroforestry practice - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The Tropical Agricultural Research and Higher Education Center’s (CATIE) ShadeMotion innovation is an open-source technology that models tree shade and can inform tree-planting practices to improve crop yields, enhance agroforest sustainability, and support climate adaptation of both farm and agro-ecosystems. ShadeMotion is intended for use by researchers (including students), farmers, and practitioners (e.g., extension staff, technicians). Integration of ShadeMotion in post-secondary curricula, training, and application in demonstration farms in Latin America supports capacity development and more sustainable agroforestry practices.